Marketing Analysis of Catch Resuts Snakehead Fish Central Muning Village, Daha Selatan Sub-District, Hulu Sungai Selatan Regency of South Kalimantan - Tri Dekayanti; Rina Mustika; Hairi Hairi (TROPICAL WETLAND JOURNAL, 2020)
This study aims to: 1). Analyzing the marketing channels of the Snakehead fish (Channa striata) catch in Central Muning Village. 2). Analyzing the potential margins of the Snakehead Fish (Channa striata) business in Central Muning Village. 3). Analyzing the part (share) price received by catching Snakehead in Central Muning Village. 4). Analyzing the feasibility of Snakehead fishing in Central Muning Village and the business feasibility of the marketing actors. The method of data collection is done by observation and interviews. The sample in this study was determined by purposive sampling method. Sampling is done by two methods: Census Sampling and Snowball Sampling. This research was conducted in the Central Muning Village, Daha Selatan Sub-district, Hulu Sungai Selatan District. The results of this study indicate that the Snakehead fish marketing system in Central Muning Village from the producer level to the final consumer level generally has 2 marketing channel patterns. Snakehead fish marketing margin in Central Muning Village in the marketing pattern I was Rp. 4000, - while the marketing margin in the marketing pattern II for collecting traders is Rp. 2000, - and for retailers Rp. 3000, -. The share value received by fishermen caught is 90%. Looking from the business feasibility analysis carried out, the business of catching Snakehead Fish in the village of Central Muning is feasible to continue.